Long-term medical and psychosocial outcomes in congenital diaphragmatic hernia survivors. Issue 8 (15th August 2019) - Tan, Jason K; Banton, Georgia; Minutillo, Corrado; Hall, Graham L; Wilson, Andrew; Murray, Conor; Nathan, Elizabeth A; Verheggen, Maureen; Ramsay, James; Samnakay, Naeem; Dickinson, Jan
Abstract : Objective: Survival rates for congenital diaphragmatic hernia (CDH) are increasing. The long-term outcomes of CDH survivors were compared with a healthy control group to assess the morbidity for guidance of antenatal counselling and long-term follow-up programmes. Participants and design: Participants born with CDH in Western Australia 1993–2008 were eligible with matched controls from the general population. Participants had comprehensive lung function tests, echocardiogram, low-dose chest CT scan and completed a Strengths and Difficulties Questionnaire (SDQ) and quality of life (QOL) questionnaire. Results: 34 matched case–control pairs were recruited. Demographic data between groups were similar. Cases were smaller at follow-up (weight Z-score of −0.2vs0.3; p=0.03; height Z-score of −0.3vs0.6; p=0.01). Cases had lower mean Z-scores for forced expiratory volume in 1 s (FEV1 ) (−1.49 vs −0.01; p=0.004), FEV1 /forced vital capacity (−1.92 vs −1.2; p=0.009) and forced expiratory flow at 25-75% (FEF25-75) (−1.18vs0.23; p=0.007). Cases had significantly worse respiratory mechanics using forced oscillation technique. Subpleural triangles architectural distortion, linear opacities and scoliosis on chest CT were significantly higher in cases. Prosthetic patch requirement was associated with worse lung mechanics and peak cough flow. Cases had significantly higher rates of gastro-oesophageal reflux disease (GORD) and GORD medication usage. Developmental delay was significantly higher in cases. More cases had a total difficulties score in the high to very high range (25% vs 0%, p=0.03) on the SDQ and reported lower objective QOL scores (70.2 vs 79.8, p=0.02). Conclusion: Survivors of CDH may have significant adverse long-term medical and psychosocial issues that would be better recognised and managed in a multidisciplinary clinic.